Chain of ideas [large type] : the origins of our authoritarian age - Kendi, Ibram X. (Random House Large Print Publishing, 2026)
"Recall the words chanted in Charlottesville, Virginia: "You will not replace us!" Recall the string of mass shooters across the globe--in Oslo, Christchurch, Buffalo, El Paso, and Pittsburgh--who claimed their crimes were a defense against "White genocide." Recall business and media figures cultivating anxiety and furor over demographic change. These incidents only scratch the surface: Popular and ruling politicians in every region of the world have expressed some version of great replacement theory, eroding democratic norms in the name of preventing demographic change. The term was coined in 2011 by a French novelist who argued that Black and Brown immigrants were "invading" Europe, brought by shadowy elites to "replace" the White population. From there, politicians and theorists in the United States and elsewhere repackaged it as a story of "globalists" welcoming "migrant criminals" and promoting diversity to take away the jobs, cultures, electoral power, and very lives of White people. Over time, great replacement theory has expanded those under threat to include citizens, men, Jews, Christians, heterosexuals, and ethnic majorities in countries as distinct as Russia, El Salvador, Brazil, Italy, and India, all targeted with the message that they are facing an existential attack that only a strongman can prevent. Ibram X. Kendi offers an unsettling but indispensable global history of how great replacement theory brought humanity into this authoritarian age--and how we can free ourselves from it." -- Page [4] cover.